Tuning of electronic properties via labile N→B-coordination in conjugated organoboranes. Issue 7 (2nd February 2017) - Schraff, Sandra; Sun, Yu; Pammer, Frank
Abstract : In this report we demonstrate that labile intramolecular N→B-Lewis pair formation can serve to tailor the properties of π-conjugated electronic materials. Abstract : In this report we demonstrate that labile intramolecular N→B-Lewis pair formation can serve to tailor the properties of π-conjugated electronic materials. A series of boranes has been prepared by copper-catalyzed 1, 3-dipolar azide–alkyne 'click'-cycloaddition with a bifunctional borane (B2 -H ), which allowed the introduction of electronically varied aryl-substituents on the triazole ring ( p -MeOPh, p -MePh, p -F3 CPh), and also the preparation of a polymer (PTrz ) with number-average molecular weight M n = 7.2 kDa (PDI = 2.1, DP n ≈ 8.2). The optical and electrochemical properties of the boranes have been investigated in detail, and complemented by DFT calculations and anion binding studies. 11 B NMR and dynamic 1 H NMR show that the N→B-coordination persists in solution but is comparatively weak, and the boranes undergo rapid thermal exchange betweenclosed, N→B-coordinated andopen, non-coordinated conformers. UV-vis-absorption spectra exhibit only a minor impact of the derivatization, while fluorescence measurements show a direct correlation between the peripheral substituents and the observed Stokes shifts (3200 to 10 000 cm −1 ), fluorescence lifetimes ( τ = 23–11 ns) and quantum yields ( φ = 17.3–6.4%). Titration with cyanide shows that the strength of the N→B-bond can be incrementally tuned by variation of the peripheral substituents, to allow for direct binding of cyanide to boron.